2012
DOI: 10.3892/ijo.2012.1392
|View full text |Cite
|
Sign up to set email alerts
|

PDEF downregulates stathmin expression in prostate cancer

Abstract: Abstract. The Ets proteins are a family of transcription factors characterized by an evolutionarily conserved DNA binding domain that controls key cellular processes. Prostate-derived Ets transcription factor (PDEF), a member of the Ets family, is reported to be present in tissues with high epithelial content, notably breast and prostate. However, the role of PDEF in cancer development is not fully understood. To gain insight into the molecular mechanisms associated with prostate cancer progression, we employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…However, several groups reported that SPDEF is a negative regulator of cell proliferation in some cancer types including prostate cancer4041. It was shown that overexpression of SPDEF in PC-3 cells inhibited proliferation and induced apoptosis via negative regulation of stathmin and survivin expression3641. Taken together with our findings, SPDEF has different roles in the regulation of androgen-sensitive and -insensitive prostate cancer cell proliferation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, several groups reported that SPDEF is a negative regulator of cell proliferation in some cancer types including prostate cancer4041. It was shown that overexpression of SPDEF in PC-3 cells inhibited proliferation and induced apoptosis via negative regulation of stathmin and survivin expression3641. Taken together with our findings, SPDEF has different roles in the regulation of androgen-sensitive and -insensitive prostate cancer cell proliferation.…”
Section: Discussionsupporting
confidence: 69%
“…Knockdown of AIbZIP , which is a direct target of SPDEF, suppressed the proliferation of prostate cancer cells, indicating that AIbZIP functions downstream of SPDEF as a major regulator of proliferation in these cells. However, several groups reported that SPDEF is a negative regulator of cell proliferation in some cancer types including prostate cancer4041. It was shown that overexpression of SPDEF in PC-3 cells inhibited proliferation and induced apoptosis via negative regulation of stathmin and survivin expression3641.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that prostate-derived Ets transcription factor (PDEF) is present in breast and prostate cells and tissues. It seems that high expression of stathmin brings down the effects that PDEF inhibit cell proliferation, colony formation and tumor migration, and discloses that PDEF exert an antitumor effects through down-regulating the expression of oncogenic stathmin [ 65 ] (Fig. 4 c).…”
Section: Introductionmentioning
confidence: 99%
“…[36] Overexpression of miR-150 in CD133 (+) TICs leads to inhibition of self-renewal and tumor growth via interaction with the 3'UTR of c-Myb mRNA. [37] miR-22 promotes Hepatitis-B virus related HCC development through down-regulation of estrogen receptor alpha (ER𝛼) transcription. [38] More interestingly, expression of these miRNAs often coincides with epigenetic changes to alter target gene expression.…”
Section: Discussionmentioning
confidence: 99%